Online Peer-to-Peer Support for Young People With Mental Health Problems: A Systematic Review - Ali, Kathina (JMIR Ment Health, 2015)
BACKGROUND: Adolescence and early adulthood are critical periods for the development of mental disorders. Online peer-to-peer communication is popular among young people and may improve mental health by providing social support. Previous systematic reviews have targeted Internet support groups for adults with mental health problems, including depression. However, there have been no systematic reviews examining the effectiveness of online peer-to-peer support in improving the mental health of adolescents and young adults. OBJECTIVE: The aim of this review was to systematically identify available evidence for the effectiveness of online peer-to peer support for young people with mental health problems. METHODS: The PubMed, PsycInfo, and Cochrane databases were searched using keywords and Medical Subject Headings (MeSH) terms. Retrieved abstracts (n=3934) were double screened and coded. Studies were included if they (1) investigated an online peer-to-peer interaction, (2) the interaction discussed topics related to mental health, (3) the age range of the sample was between 12 to 25 years, and (4) the study evaluated the effectiveness of the peer-to-peer interaction. RESULTS: Six studies satisfied the inclusion criteria for the current review. The studies targeted a range of mental health problems including depression and anxiety (n=2), general psychological problems (n=1), eating disorders (n=1), and substance use (tobacco) (n=2). The majority of studies investigated Internet support groups (n=4), and the remaining studies focused on virtual reality chat sessions (n=2). In almost all studies (n=5), the peer support intervention was moderated by health professionals, researchers or consumers. Studies employed a range of study designs including randomized controlled trials (n=3), pre-post studies (n=2) and one randomized trial. Overall, two of the randomized controlled trials were associated with a significant positive outcome in comparison to the control group at post-intervention. In the remaining four studies, peer-to-peer support was not found to be effective. CONCLUSIONS: This systematic review identified an overall lack of high-quality studies examining online peer-to-peer support for young people. Given that peer support is frequently used as an adjunct to Internet interventions for a variety of mental health conditions, there is an urgent need to determine the effectiveness of peer support alone as an active intervention.